Förvaringsanordning för strålskyddsprodukt mellan operationer - Olsson, Maja; Lilja, Josefin (My University, 2025)
MasterPeace is a radiation protection product used during minimally invasive surgeries to reduce healthcare staff’s exposure to ionizing radiation. Currently, there is no dedicated storage system for this product, which this thesis aims to investigate. The project was carried out in collaboration with Texray AB and was based on study visits, including observations and interviews with healthcare professionals at Sahlgrenska Universitetssjukhuset and Hallands Sjukhus Varberg. Following this, idea and concept generation was conducted to develop a solution that improves the working environment and workflow by simplifying the handling and storage of MasterPeace. Evaluation methods were then used to select a concept, which was further refined and optimized in dialogue with users. To ensure stability, calculations were also performed on the final concept. The result is a mobile stand that stores MasterPeace with the flexibility to be repositioned for space optimization in the operating room. MasterPeace is hung using eyelets located in the corners of the product, which simplifies handling and improves drying capability. The final concept thus contributes to a more ergonomic, time-efficient and simplified use of MasterPeace